Variasi Fungsi Penerapan Ekoenzim dari Limbah Organik: Tinjauan Literatur - Muhammad Daffa Fadlurrahman; Martha Aznury (Center for Pulp and Paper, 2022)
Various Application of Eco-enzymes from Organic Waste: A ReviewAbstractRecycling is an effective waste-handling method to utilize. One of the products of the process of recycling is eco-enzymes. Eco-enzymes is a fermented liquids from mixed organic waste and molasses. The eco-enzymes fermentation process usually takes 90 days or more to produce the optimal number of enzymes. In our daily life, eco-enzymes could be used for various applications. Eco-enzyme’s abilities to reduce various impurities in water makes eco-enzymes an alternative water purification. Aside from being a water purification, eco-enzymes can also be used as hand sanitizers and disinfectants because they have bactericidal properties. Ecoenzymes can also be used as fertilizers and soil conditioners because they contain high levels of nitrogen, phosphorus, potassium, and so many other benefits.Keywords: eco-enzymes, function, applicationAbstrakDaur ulang merupakan metode penanganan sampah yang efektif untuk digunakan. Salah satu produk dari proses daur ulang ialah ekoenzim. Ekoenzim merupakan cairan hasil fermentasi dari limbah organik dan molase. Proses fermentasi ekoenzim biasanya sekitar 90 hari atau lebih untuk menghasilkan enzim yang optimal. Dalam kehidupan sehari-hari, ekoenzim dapat dimanfaatkan untuk berbagai hal. Kemampuan ekoenzim mengurai berbagai unsur pengotor air menjadikan ekoenzim sebagai salah satu alternatif media penjernih air. Selain sebagai media penjernih air, ekoenzim juga dapat dimanfaatkan sebagai panyanitasi tangan (hand sanitizer) dan disinfektan karena memiliki sifat bakterisid. Ekoenzim juga dapat dimanfaatkan sebagai pupuk dan pembenah tanah karena mengandung nitrogen, fosfor, dan kalium yang cukup tinggi serta masih banyak manfaat lainnya.Kata Kunci: ekoenzim, fungsi, penerapan